Analyzing the Applicability of Preschool Curriculum Using Children’s Songs from the Perspective of Preschool Teachers: An example of the Song “Taxi Tango” - Mei-Ying Liao; Martin Bernard Lu (International Journal of Social Sciences and Artistic Innovations)
We explored the characteristics of children’s songs appropriate for adaptive curriculum from the perspective of Preschool teachers using the song ‘Taxi Tango’. Semi-structured interviews were conducted with six preschool teachers who used ‘Taxi Tango’ in teaching. These preschool teachers lacked specialized musical backgrounds and exhibited a positive attitude toward aesthetic education. Their teaching encompassed various age groups of students and employed instructional approaches such as thematic teaching, project-based teaching, and learning center-based teaching. A shared enthusiasm for ‘Taxi Tango’ among preschoolers and preschool teachers was found. Preschool teachers highlighted the song’s high repetition in lyrics and melody and the dynamic musical elements for aesthetic education within the curriculum. The distinctive dynamic design of the song contributed to the creation of diverse musical activities and enhanced the quality of teaching and motivation. The song’s unique dynamic design fostered independent learning and exploration among preschoolers and cultivated music exploration and expression. A children’s song appropriate for education must be simple and comprehensible with distinctive musical characteristics for aesthetic education through diverse activities.